Original articleMutations in the exon 7 of Trp53 gene and the level of p53 protein in double transgenic mouse model of Alzheimer’s disease - Dorszewska, Jolanta; Oczkowska, Anna; Suwalska, Monika; Rozycka, Agata; Florczak-Wyspianska, Jolanta; Dezor, Mateusz; Lianeri, Margarita; Jagodzinski, Pawel P.; Kowalczyk, Michal J.; Prendecki, Michal; Kozubski, Wojciech (Folia Neuropathologica, 2014)
Alzheimer’s disease (AD) leads to generation of β-amyloid (Aβ) in the brain. Alzheimer’s disease model PS/APP mice show a markedly accelerated accumulation of Aβ, which may lead to apoptosis induction e.g. in cells expressing wild-type p53. The TP53 gene is found to be the most frequently mutated gene in human tumour cells. There is accumulating evidence pointing out to the contribution of oxidative stress and chronic inflammation in both AD and cancer. The purpose of this study was to analyze exon 7 mutations of the murine Trp53 gene and Aβ/A4 and p53 protein levels in PS/APP and control mice. The studies were performed on female double transgenic PS/APP mice and young adults (8-12 weeks old) and age-matched control mice. The Trp53 mutation analysis was carried out with the use of PCR and DNA sequencing. The Aβ/A4 and p53 levels were analyzed by Western blotting. The frequency of mutations was almost quadrupled in PS/APP mice (44%), compared to controls (14%). PS/APP mice with the A929T and A857G mutations had a similar p53 level. In cerebral gray matter of PS/APP mice the level of p53 positive correlated with the level of Aβ protein (R S = +0.700, p < 0.05). In younger control animals, the T854G mutation was related to p53 down-regulation, while in aging ones, G859A substitution was most likely associated with over-expression of p53. In silico protein analysis revealed a possibly substantial impact of all four mutations on p53 activity. Three mutations were in close proximity to zinc-coordinating cysteine residues. It seems that in PS/APP mice missense Trp53 exon 7 mutations may be associated with the degenerative process by changes of p53 protein function.